The Pediatric Oncology East and Mediterranean (POEM) group - A regional collaborative platform for childhood cancer healthcare professionals - Raya Saab; Asim Belgaumi; Samar Muwakkit; Anas Obeid; Carlos-Rodriguez Galindo; Sima Jeha; Abdul-Ha (Elsevier, 2020)
The Pediatric Oncology East and Mediterranean (POEM) group was established in 2013 as a cooperative platform for physicians, scientists and healthcare professionals from institutions in the East and Mediterranean area with the goal of sharing experiences, initiating cooperative trials and establishing common strategies to achieve optimization of the care of pediatric oncology patients in the region. The mission of POEM group is to continuously improve pediatric oncology care, research, training and advocacy in the East and Mediterranean region by means of integrated teamwork. Our Vision is to be the leading pediatric oncology collaborative group in the East and Mediterranean Region. POEM group is currently at more than 550 registrants from 119 centers in 28 countries regionally. This review summarizes the structure and activities of POEM group since its inception, and highlights identified challenges and future plans. Keywords: Pediatric oncology, Collaborative group, LMIC